2007
DOI: 10.1590/s0034-89102006005000039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tobacco use in individuals with severe mental illnesses, São Paulo, Brazil

Abstract: OBJECTIVE: To analyze the prevalence of cigarette smoking in individuals with severe mental illnesses in a large urban centre of a middle income country. METHODS: Cross-sectional study carried out in São Paulo. The sample (N=192) comprised individuals diagnosed with severe mental illnesses who had contact with public psychiatric care services from September to November 1997 and were aged between 18 and 65 years. Prevalence of daily tobacco smoking in the 12 months previous to the interview and characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(38 reference statements)
2
8
0
2
Order By: Relevance
“…As in other studies, an association was found between current smoking and several sociodemographic characteristics, including being male, older age, low education level 6,11,13,14,16 , and history of homelessness 40,41 , while a negative association was found between smoking and practicing a religion 42,43 . A low level of education may be considered a marker for low access to knowledge and understanding of the harmful effects of tobacco 16 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As in other studies, an association was found between current smoking and several sociodemographic characteristics, including being male, older age, low education level 6,11,13,14,16 , and history of homelessness 40,41 , while a negative association was found between smoking and practicing a religion 42,43 . A low level of education may be considered a marker for low access to knowledge and understanding of the harmful effects of tobacco 16 .…”
Section: Discussionsupporting
confidence: 78%
“…An association has been found between smoking and severe mental illness (schizophrenia, bipolar disorders and other psychoses), markers for clinical severity (e.g. previous hospitalization) and substance use disorders 11,12,13,14,15 . However, the nature of these associations is not always clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies with schizophrenia patients report that cigarette use is associated to male gender (30)(31)(32)(33)(34). Smoking is also associated with male sex not only in people with schizophrenia but with other mental illnesses as well (35)(36)(37). Males have a higher smoking rate also in the general public sample (29).…”
Section: Discussionmentioning
confidence: 97%
“…Contrariamente, tal associação parece mais evidente quando estudada em grupos populacionais específicos. Em estudos sobre o uso de tabaco, por exemplo, quando desenvolvidos com grupos de pacientes com diagnósticos definidos de alguns transtornos mentais, institucionalizados, moradores de rua ou em tratamento ambulatorial, a associação entre o consumo de SPA e a ocorrência de sofrimento psíquico mostra-se mais evidente (De Leon, Becoña, Gurpegui, Gonzalez-Pinto & Diaz, 2002;Leonard, Adler, Benhammou, Berger, Breese et al, 2001;Ratto, Menezes & Gulinelli, 2007;Usdan, Schumacher, Milby, Wallace, McNamara et al, 2001). Outro exemplo é o fato de que a ocorrência de tentativas de suicídio, em países em desenvolvimento, pode ter como fator preditivo de sua ocorrência o consumo de SPA (Nock, Hwang, Sampson, Kessler, Angermeyer et al, 2009).…”
Section: Discussionunclassified